2021
DOI: 10.1038/s41392-021-00799-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of in situ CRISPR-mediated primary and metastatic cancer from monkey liver

Abstract: Non-human primates (NHPs) represent the most valuable animals for drug discovery. However, the current main challenge remains that the NHP has not yet been used to develop an efficient translational medicine platform simulating human diseases, such as cancer. This study generated an in situ gene-editing approach to induce efficient loss-of-function mutations of Pten and p53 genes for rapid modeling primary and metastatic liver tumors using the CRISPR/Cas9 in the adult cynomolgus monkey. Under ultrasound guidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Unfortunately, the absence of spontaneous orthotopic tumor model hinders this progression of new drugs. Zhong and coworkers [ 151 ] evaluated ultrasound-guided infusion of CRISPR-Cas9 into the liver of cynomolgus monkeys via the intrahepatic portal vein. They demonstrated that Pten and p53 gene mutations could be efficiently generated in the liver of these monkeys through intrahepatic portal vein injection of the CRISPR-Cas9 genome editing system.…”
Section: Emerging Technology For Serving Ovs In Elevating Antitumor E...mentioning
confidence: 99%
“…Unfortunately, the absence of spontaneous orthotopic tumor model hinders this progression of new drugs. Zhong and coworkers [ 151 ] evaluated ultrasound-guided infusion of CRISPR-Cas9 into the liver of cynomolgus monkeys via the intrahepatic portal vein. They demonstrated that Pten and p53 gene mutations could be efficiently generated in the liver of these monkeys through intrahepatic portal vein injection of the CRISPR-Cas9 genome editing system.…”
Section: Emerging Technology For Serving Ovs In Elevating Antitumor E...mentioning
confidence: 99%
“…As expected, the model monkey died shortly after birth and displayed severe developmental retardation. A recent study reported a new method to generate gene-modified monkeys by in situ CRISPR-mediated technique ( Zhong et al, 2021 ). This study utilized CRISPR/Cas9 to knock down Pten and p53 genes in adult cynomolgus, thus modeling primary and metastatic liver tumors rapidly, which was effective in situ gene editing approach.…”
Section: Application Of Crispr/cas9 Gene Editing Technology In Nhpsmentioning
confidence: 99%
“…Due to the characteristics of simple composition and high editing efficiency [ [4] , [5] , [6] ], it has rapidly gained popularity and become as a hallmark in biomedicine field. CRISPR/Cas9 can be universally applied to a wide range of biological studies, including nonhuman primates [ 7 ], mice [ 8 ], rat [ 9 ], zebra fish [ 10 ], Drosophila [ 11 ], helminth [ 12 ], as well as a myriad of common plants [ 13 ] and microbes [ 14 ]. CRISPR/Cas9 gene editing has found widespread application, however, there remains no definitive conclusion regarding whether the process of gene editing and repair can potentially induce harmful effects on the genome.…”
Section: Introductionmentioning
confidence: 99%